Comparative Study of Common Bile Duct Diameter between Normal and Post Cholecystectomy Cases Using Trans-abdominal Ultrasonography - Paudel, R. C.; Karki, S.; Suwal, S.; Palikhe, A.; Mandal, D.; Manandhar, M. (Kathmandu University Medical Journal, 2022)
Background Increase in common bile duct diameter can occur because of different causes. Post cholecystectomy status is one of the potential causes. Many studies done in the past show different results and are hence inconclusive. Objective To see if the post cholecystectomy cases would have a statistically significant change in common bile duct diameter. Method We carried out a study in 100 cases (46 post cholecystectomy cases and 54 cases with intact gall bladder, measuring their common bile duct diameters and performing an unpaired t test to see if the mean in common bile duct among these two groups of cases was statistically significant. Result One hundred cases, 46 post cholecystectomy cases and 54 cases with intact gall bladder were included in our study. An unpaired t-test was used to compare the common bile duct diameters in these two groups. Our findings showed that the difference in common bile duct diameter between the cases with intact gall bladder and those who underwent cholecystectomy was significant for both one tailed and two tailed studies (p < 0.001). Hence, it can be stated that post cholecystectomy status increases the common bile duct diameter. Conclusion An increased Common bile duct diameter in post cholecystectomy case could be because of the post cholecystectomy status itself and not due to some other obstructive cause. So careful decision is necessary before subjecting the patient to further invasive/non-invasive investigations and treatments.